2020
DOI: 10.3390/w12030737
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Seismic Cone Penetration Test (SCPTU) in Tailings Water Conditions Monitoring

Abstract: The safe operation of the large, outflow Tailings Storage Facilities (TSF) requires comprehensive and continuous threat monitoring. One of the basic kinds of threat monitoring is to monitor the water conditions in deposited tailings, which is usually carried out using a conventional piezometric observation method from a network of installed piezometers. In complex tailings storage conditions, the reliability of the piezometric method may be questioned. The Seismic Cone Penetration Test (SCPTU) can meet high te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The Żelazny Most Tailings Storage Facility (Figure 1) was put into operation on 12 February 1977, during the final phase of the Gilów storage operation. The storage facility is located within the territories of three municipalities belonging to two counties in the Lower Silesian Voivodeship (51.515634 N, 16.207030 E).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The Żelazny Most Tailings Storage Facility (Figure 1) was put into operation on 12 February 1977, during the final phase of the Gilów storage operation. The storage facility is located within the territories of three municipalities belonging to two counties in the Lower Silesian Voivodeship (51.515634 N, 16.207030 E).…”
Section: Study Sitementioning
confidence: 99%
“…The elements of geotechnical monitoring mainly consist of specialized in situ tests, deep drilling, a geodetic network, GPS stations, an inclinometer network, a seismometric network, a piezometer network, and others [13][14][15][16][17]. An extensive monitoring database allows for the assessment of the actual response of the storage facility to the substrate.…”
Section: Study Sitementioning
confidence: 99%
“…For example, Fellenius (2015) [22] indicated that the pile toe resistance calculated from CPT results can considerably overestimate the actual value measured in field tests. Besides, CPTs are normally limited up to 50 m depth [21,62], whereas large bored piles can easily exceed this depth, causing a lack of method to estimate the shaft and base resistances for these long piles. These limitations of past ANN models require a more rigorous determination of influencing factors on the bearing capacity of piles that can be used as the key input parameters for establishing the model.…”
Section: Introductionmentioning
confidence: 99%
“…The soil property can be inferred by analyzing the stress of the probe at different depths. Because of the low cost and high reliability, CPT has been widely used in the field of geological exploration, such as in underground soil testing [ 1 ], building foundation monitoring, groundwater monitoring [ 2 , 3 , 4 , 5 , 6 , 7 ], and assessments of effective stress state in soils [ 8 ]. Typically, the sensing device for underground exploration is a probe with a cone-shaped tip, and various sensors can be installed inside the probe [ 9 ].…”
Section: Introductionmentioning
confidence: 99%